Fundamentals of Systematic Reflection in Practice: How Reflective Practice Effect Professional Identity Formation and Lifelong Learning - Bundgaard, Stine Bylin; Johansson, Nicolaj (Proceedings for the European Conference on Reflective Practice-based Learning 2025, 2025)
In a world characterized by constant change and complexity, the need for a strong professional identity and the ability to act as a reflective practitioner has become more crucial than ever. This article explores how systematic reflection can support lifelong learning and professional identity formation, focusing on a pilot study conducted in the Diploma in Leadership at UCN. The study involved the use of reflection portfolios as both a learning tool and empirical data, with students documenting their learning activities and reflections. Through semi-structured interviews and focused content analysis, the study aimed to develop and qualify a reflection model that highlights the connection between learning, reflection, and professional identity formation. The reflection model presented includes four levels: learning moments, recognition, transformation, and professional identity. Each level is described in detail, with examples from the pilot study illustrating how students used the reflection levels to become aware of their learning and development. The model aims to scaffold the movement from initial aha moments to more conscious and transformative reflections, contributing to the formation of professional identity. The findings suggest that systematic reflection can significantly impact students’ reflective skills, awareness of their own learning, and professional identity formation. By integrating reflection as a central part of education, students can navigate a complex world with greater confidence, competence, and reflexivity. The article concludes with didactic reflections on how the model can be used in higher education to support lifelong learning and professional identity formation.